2021
DOI: 10.3961/jpmph.21.384
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Social Activities and Living Arrangements on Cognitive Functions in Middle-aged and Elderly Adults: A Panel Study Using the 2006-2018 Korean Longitudinal Study of Aging

Abstract: Objectives: Previous studies have shown that participation in social activities (SA) can prevent cognitive decline (CD) and that living arrangements (LA) can affect cognitive function. This study aimed to evaluate the effects of SA and LA on CD, as well as their interactions, using longitudinal data.Methods: Data were used from the 2006-2018 Korean Longitudinal Study for Aging, which followed 10 254 adults older than 45 years over a 12-year period. CD was defined as a ≥4-point score decrease in the Mini-Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(29 reference statements)
1
9
0
Order By: Relevance
“…As few studies simultaneously included handgrip strength, depression, social participation, and cognitive function in older adults with cardiovascular diseases, we could not directly compare our findings with previous studies. However, our results were consistent with cross‐sectional studies (Bae, 2020; Choi et al, 2021). Notably, Bae (2020) showed that community‐dwelling older adults over 60 with high handgrip strength, low depression, and attending social participation had better cognitive functioning.…”
Section: Discussionsupporting
confidence: 93%
“…As few studies simultaneously included handgrip strength, depression, social participation, and cognitive function in older adults with cardiovascular diseases, we could not directly compare our findings with previous studies. However, our results were consistent with cross‐sectional studies (Bae, 2020; Choi et al, 2021). Notably, Bae (2020) showed that community‐dwelling older adults over 60 with high handgrip strength, low depression, and attending social participation had better cognitive functioning.…”
Section: Discussionsupporting
confidence: 93%
“…Atsushi's [29] study found that half of sampled bereaved seniors transitioned to living alone after 2013. Choi and colleagues [30] also revealed a significant increase in the number of living alone groups from 2006 to 2018 among Korean older adults. By conducting an APC analysis of Chinese sample, scholars indicated that older adults' willingness to live alone rose gradually till 2011 and it stayed flat afterwards [31].…”
Section: Changing Patterns Of Living Arrangements Among Older Adultsmentioning
confidence: 92%
“…The score ranges from 0 to 30. Based on previous studies, we categorized those with a score of 23 or less as having cognitive impairment and those with a score of 24 or more as having normal cognition [13][14][15].…”
Section: Cognitive Impairmentmentioning
confidence: 99%